2010
DOI: 10.1103/physrevlett.105.216801
|View full text |Cite
|
Sign up to set email alerts
|

Correlation-Hole Induced Paired Quantum Hall States in the Lowest Landau Level

Abstract: A theory is developed for the paired even-denominator fractional quantum Hall states in the lowest Landau level. We show that electrons bind to quantized vortices to form composite fermions, interacting through an exact instantaneous interaction that favors chiral p-wave pairing. There are two canonically dual pairing gap functions related by the bosonic Laughlin wavefunction (Jastrow factor) due to the correlation holes. We find that the ground state is the Moore-Read pfaffian in the long wavelength limit for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The well width can even lead to the formation of novel FQHSs, such as the ones observed at ν = 1/2 and 1/4 in the lowest LL. [18][19][20][21] The reminiscence with even-denominator states in bilayer quantum Hall systems 22 hints at a multi-component origin later confirmed theoretically both for symmetric [23][24][25][26][27] and asymmetric 28,29 quantum wells in terms of a (331) Halperin state 30 that competes with the compressible composite-fermion Fermi liquid (CFFL) 31 and, under certain circumstances, 24,25,28,32 with a Pfaffian. 5,6 Furthermore, these liquid phases compete with an insulating phase in the limit of very large well widths.…”
Section: Introductionmentioning
confidence: 82%
“…The well width can even lead to the formation of novel FQHSs, such as the ones observed at ν = 1/2 and 1/4 in the lowest LL. [18][19][20][21] The reminiscence with even-denominator states in bilayer quantum Hall systems 22 hints at a multi-component origin later confirmed theoretically both for symmetric [23][24][25][26][27] and asymmetric 28,29 quantum wells in terms of a (331) Halperin state 30 that competes with the compressible composite-fermion Fermi liquid (CFFL) 31 and, under certain circumstances, 24,25,28,32 with a Pfaffian. 5,6 Furthermore, these liquid phases compete with an insulating phase in the limit of very large well widths.…”
Section: Introductionmentioning
confidence: 82%
“…Thus, the large distance behaviors of the pairing wavefunction are g 1 (r) ∝ 1/z + c √ 2/π cos(κr − π/4)/z √ r and g 2 (r) ∝ −c √ 2/π cos(κr − π/4)/z √ r, where c and κ are numerical constants. The oscillatory terms in the above equations are due to the k 2 terms in the expansions, originating from the k dependence of the mass, which should be distinguished from the oscillatory wavefunction in [40]. The many-body real space wavefunction for CDFs can be obtained by [39] CDF…”
Section: Paired Quantum Hall Statesmentioning
confidence: 99%
“…The oscillatory terms in the above equations are due to the k 2 terms in the expansions, originating from the k dependence of the mass, which should be distinguished from the oscillatory wave function in Ref. 40 . The many-body real space wave func-tion for CDFs can be obtained by…”
Section: Paired Quantum Hall Statesmentioning
confidence: 99%
“…Similar to the case of ν = 5/2 FQHE, different topological orders have been proposed to describe the ν = 1/4 FQH state [36,[38][39][40][41][42][43]. The original experiment by Luhman et al [31] reported that the FQH state was strengthened by tilting the sample in a magnetic field.…”
Section: Introductionmentioning
confidence: 99%